2018
DOI: 10.17265/1539-8080/2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Students’ Reading Comprehension and Their Achievement in English

Abstract: This study aimed at investigating the relationship between students' reading comprehension and their achievement in English at Yarmouk University. The sample consisted of 150 female and male students. It was chosen randomly from all English101 students at Yarmouk University in the second semester of the academic year 2016-2017. To answer the questions of the study, the researcher used a reading comprehension test which consisted of 20 multiple-choice items and an achievement test which consisted of 40 multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…On the other hand, the findings imply that high academic achievement is highly associated with higher reading skills performance as high achievers in both urban and rural settings scored higher results in the reading skill test. In line with this, many researchers such as Keskin [46], Yıldız [47], Kerubo [29], and Hijazi [48] disclosed that there was a statistically significant relationship between students' reading comprehension and their achievement in English since reading comprehension positively affects students' achievement. Besides, Sholihah [49] specifically highlights that urban students are interested much in reading the text related to academics like science and new technologies, for example, texts related to computers, Internet, and mobile phones, whereas the students of rural areas have tended to receive a text that is derived from the teacher only.…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, the findings imply that high academic achievement is highly associated with higher reading skills performance as high achievers in both urban and rural settings scored higher results in the reading skill test. In line with this, many researchers such as Keskin [46], Yıldız [47], Kerubo [29], and Hijazi [48] disclosed that there was a statistically significant relationship between students' reading comprehension and their achievement in English since reading comprehension positively affects students' achievement. Besides, Sholihah [49] specifically highlights that urban students are interested much in reading the text related to academics like science and new technologies, for example, texts related to computers, Internet, and mobile phones, whereas the students of rural areas have tended to receive a text that is derived from the teacher only.…”
Section: Discussionmentioning
confidence: 83%
“…Menaka and Jebaraj (2017), in their study, a conclusion was made on the correlation between the students' comprehension in reading and their achievement in English. Same to Hijazi (2018), it was found that reading comprehension positively affects English achievement. Hence, reading enrichment activities should be formulated to enhance the students' reading skills as this has a positive effect on their English grades.…”
Section: Language Skillsmentioning
confidence: 88%
“…The mastery of both receptive and productive vocabulary knowledge is indeed essential for the young learners' academic success (Hijazi, 2018;Nation, 1993;Qian & Lin, 2019). Nevertheless, the teaching and learning of vocabulary is often untended in the field of applied linguistics (Alqahtani, 2015;Schmitt, 2010) as well as school syllabus (Folse & Briggs, 2004).…”
Section: Central Importance Of Esl Vocabulary In Language Learningmentioning
confidence: 99%